Rationality of Extension of Term of Office of Notary Public - Jannah, Roudlatul; Alfath, Tahegga Primananda (Dinasti Research, 2025)
The retirement age for the position of Notary, as stipulated in Article 8 paragraph (1) letter b and Article 8 paragraph (2) of Law No. 30 of 2004 on the Position of Notary, explicitly limits the maximum age for holding the position to 65 (sixty-five) years. However, an extension may be granted up to 67 (sixty-seven) years. The Constitutional Court considers this retirement age regulation to be